Urgensi Reformasi Hukum Pidana Indonesia dalam Menjerat Pelaku Deepfake Pornografi Berbasis Artifical Intellegence - Zafna Haefani, Hayya; SRI MULYANTI, Asti (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2025)
Advances in Artificial Intelligence (AI) technology have had an impact in many sectors, including in the field of crime. One of the most alarming acts of abuse of artificial intelligence today is the creation and dissemination of pornographic deepfake content. Deepfake is an audio-visual content that in reality manipulates a person's face or body without their permission. This phenomenon interferes with the privacy of victims and has serious psychological and social impacts. However, the laws that regulate the criminal law system in Indonesia are still very minimal and do not have a specific article that regulates this crime, on the other hand, this creates a legal vacuum in criminal law enforcement. This article aims to examine the urgency of criminal law reform by using normative juridical methods with progressive steps that are responsive to the speed of technological development for artificial intelligence-based deepfake pornography crime cases. The results of the study show that there are still many material and formal aspects that must be changed or added in the